INTEGRASI HADIS DAN SASTRA ARAB DALAM KITAB AMTSAL AL-HADITS KARYA AR-RAMAHURMUZI - Binti Jamaluddin, Muhajirah (AL MA'ANY, 2023)
????? ??????? ?? ????? ????? ??????? ???? ???? ??????? ?????. ?? ???? ?????? ???????? ???? ??????? ?????? ????? ?????? ????? ???? ????? ????? ???? ????? ????? ?????? ??????? ????? ????. ???? ??? ?????? ???????? ???? ??????? ????????? ??? ?????? ??? ????? ?????? ?????? ?????? ?? ???? "????? ??????" ???????????? ?? ??????? ??? ???? ????? ????? ?? ?????? ?? ????. ????? ???? ??????? ?? ???? ?????? ???? ????? ???? ??? ?????? ????? ??? ??? 137 ?????? ?? ??? 140 ????? ????? ??????????? ??????. ????? ??? ?????? ?????? ?? ?????? ???? ???? ?? ???????? ???? ????? ??????????? ????? ?????? ??????? ??? ???????? ?????????? ??????????? ??????? ???????? ????????. Abstrack The presence of Islam did not necessarily eradicate Arabic literature, which had become a tradition of the Arab people. Through the Qur'an and Hadith, literary stylistics has become a scientific treasure preserved by the presence of prophetic rhetoric with the characteristics of jawami' al-kalam as the prerogative of Prophet Muhammad. This research, using the literature review method, aims to identify the integration of hadith and Arabic literature contained in the book "Amtsal al-Hadith" by ar-Ramahurmuzi, with his role as a writer and hadith expert in his time. The results can be observed from the copy of the book edited by Ahmad 'Abd al-Fattah Tamam, which found 137 hadiths among the 140 narrations written by Ramahurmuzy with isnad. The integration of Hadith and literature in the book is explicitly reflected in the themes that Ramahurmuzi compiled, incorporating literary elements such as amtsal, kinayah, tasybih, na't, mutsanna, and nawadir.